Flora of Bokor National Park, Cambodia VI: A new species of Wikstroemia (Thymelaeaceae), W. bokorensis - Oguri, Emiko; Tagane, Shuichiro; Chhang, Phourin; Toyama, Hironori; Murakami, Noriaki; Yahara, Tetsukazu (Phytotaxa, 2017)
A new species, Wikstroemia bokorensis (Thymelaeaceae), from Bokor National Park, Kampot Province, Cambodia, is described and illustrated. This species is morphologically most similar to W. nutans distributed in southern China and Vietnam, but differs in having pubescent branches and leaves, smaller anthers, a single disk scale, and glabrous ovary. DNA barcodes of ITS, rbcL, trnT-F, rps16, and rpl16 regions for the new species are also provided.